Advances in regulating physicochemical properties of mesoporous silica nanocarriers to overcome biological barriers. (15th March 2021) - Wang, Yumei; Gou, Kaijun; Guo, Xianmou; Ke, Jia; Li, Sanming; Li, Heran
Abstract: Mesoporous silica nanoparticles (MSNs) with remarkable structural features have been proven to be an excellent platform for the delivery of therapeutic molecules. Biological barriers in various forms (e.g., mucosal barrier, cellular barrier, gastrointestinal barrier, blood-brain barrier, and blood-tumor barrier) present substantial obstacles for MSNs. The physicochemical parameters of MSNs are known to be effective and tunable not only for load and release of therapeutic molecules but also for their biological responsiveness that is beneficial for cells and tissues. This review innovatively provides a description of how and why physicochemical properties (e.g., particle size, morphology, surface charge, hydrophilic-hydrophobic property, and surface modification) of MSNs influence their ability to cross the biological barriers prior to reaching targeted sites. First, the structural and physiological features of biological barriers are outlined. Next, the recent progresses in the critical physicochemical parameters of MSNs are highlighted from physicochemical and biological aspects. Surface modification, as an important strategy for achieving rapid transport, is also reviewed with special attention to the latest findings of bioactive groups and molecular mechanisms. Furthermore, advanced designs of multifunction intelligent MSNs to surmount the blood-tumor barrier and to actively target tumor sites are demonstrated in detail. Lastly, the biodegradability and toxicity of MSNs are evaluated. With perspectives for their potential application and biosafety, the clues in summary might lead to drug delivery with high efficiency and provide useful knowledge for rational design of nanomaterials. Graphical abstract: Image, graphical abstract